Prevalence of Anemia Among Pregnant Women in Rural Village of Sindhupalchowk District of Nepal - A Cross-Sectional Study - Biyas Thapa; Smriti Bohara; Sistu KC; Madan Sapkota; Bibek Dhakal; Binod Gaire (University Library System, University of Pittsburgh, 2022)
Background: Anemia is a global public health problem all around the world, principally the developing countries like Nepal. Anemia results in maternal mortality alongside low birth weight which contributes to an increased infant mortality rate. The prevalence of anemia ranges from 27% to 42% among pregnant women depending on geographical regions. Iron and folic acid tablets are supplied free of charge to pregnant women as part of the Nepal government's National Anemia Control Strategy and Iron Intensification Program.  Methods:  A cross-sectional study was carried out among pregnant women attending Manekharka health center for an antenatal checkup. Hemoglobin levels of pregnant women from April 2018-2020 were obtained and analyzed. Hemoglobin level was determined using the indirect cyanmethemoglobin method. Results:  We used the World Health Organization (WHO) standard classification of hemoglobin levels below 11 gm/dl to determine the prevalence of anemia in pregnant women. The result suggested that a total of 30.7%, (n=63) of the pregnant women were anemic. Among which 4.76% had moderate anemia (hemoglobin 7-9.9gm/dl) and 96.58% had mild anemia (hemoglobin ≥9.9mg/dl to <11gm/dl). Conclusion:  The study and its results suggest that the women in the age group 16-19 had a higher prevalence of anemia whereas the age group 25-29 had the lowest prevalence of anemia. Moreover, the study revealed that the prevalence of anemia in hills is substantial.